Acceptance and Commitment Therapy in Adolescents with Social Phobia - Titik Dyah Agustini; Yunias Setiawati; Sasanti Yuniar; Lestari Basuki (Journal of Clinical and Cultural Psychiatry, 2023)
All health issues in the Sustainable Development Goals (SDGs) are integrated into one goal: ensuring a healthy life and promoting well-being for everyone of all ages, which includes mental health. Social phobia is a mental health problem often associated with adolescents. Social phobia is an irrational fear of negative views of others. Adolescents with social phobia will be distracted in their daily activities socially and lose their learning because they avoid interactions that cause academic problems in school. Adolescent girls experience more social phobia than adolescent boys. Biological and environmental factors are the cause of social phobia in adolescents. Social phobia management includes psychopharmaceuticals, cognitive therapy, deep breathing, Acceptance and Commitment Therapy (ACT). Currently, ACT is more recommended for use in relieving adolescents suffering from a social phobia in addition to cognitive therapy.